Reshaping Food Systems to improve Nutrition and Health in the Eastern Mediterranean Region - Al Jawaldeh , Ayoub (Open Book Publishers, 2023)
This detailed and comprehensive study examines nutrition and health in the World Health Organization (WHO) Eastern Mediterranean Region, presenting the six game-changing food systems actions proposed by the WHO and the progress of their implementation in the region. The WHO Eastern Mediterranean Region is a particularly complex place to study: an area of economic contrasts with changing dietary patterns and stark differences between high levels of malnutrition and a prevalence of overweight and obesity. As a result, actions to improve the nutritional situation of the population are urgently sought. The strategies explored in this book offer a unique opportunity to change food systems all over the world, addressing aspects including sustainable food production, the impact of marketing and labelling on behaviour, and the effect of global events such as climate change, war and the COVID-19 pandemic. Reshaping Food Systems is an essential read at a time when malnutrition in all its forms, including undernourishment, micronutrient deficiencies and overweight and obesity, pose a serious threat to global health, and is of particular interest for policymakers working in nutrition and public health.